Anti-Listeria monocytogenes biofilm mechanism of cold nitrogen plasma. (January 2021) - Cui, Haiying; Li, Hong; Abdel-Samie, Mohamed A.; Surendhiran, Duraiarasan; Lin, Lin
Abstract: In this study, the anti- L monocytogenes biofilm mechanism of cold nitrogen plasma (CNP) treatment by the generation of reactive oxygen species (ROS) and the changes of gene expression were explored. The treatment of L. monocytogenes (EDG-e, cultured in peptone yeast glucose) biofilm by CNP (600 W, for 220 s, at a gas flow rate of 100 SCCM) led to intracellular oxidative stress where ROS contents increased to 15.38% and the CNP-generated hydroxyl free radicals increased. It also indicated that CNP could activate the environmental response factor (σ B ) and the expression of s igB was increased by 3.43 times . Real-time PCR revealed that CNP treatment could inhibit the transcription levels of quorum sensing-related genes ( agrA, agrB, agrC, agrD, pfs and luxS ) and the two pathogenicity island genes ( prfA, plcA, hly, actA, plcB, inlA and inlB ) in L. monocytogenes . Finally, the application of CNP on cantaloupe preservation indicated that CNP can eliminate the biofilm of L. monocytogenes (approximately 10 8  CFU/cm 2 ) on cantaloupe by 2–3 log CFU/cm 2, thus CNP was proved as a feasible technology to reduce the risk of L. monocytogenes contamination on cantaloupe without affecting the peel color. Highlights: L. monocytogenes biofilm was effectively eliminated by cold nitrogen plasma (CNP) treatment at 600 W for 220 s. CNP stimulated the environmental response factor sigmaB of L. monocytogenes three-fold over control. CNP decreased the expression of quorum sensing-related genes of L. monocytogenes by 16%–53%.